2010
DOI: 10.1152/ajplung.00161.2009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of suppression of alveolar epithelial cell GM-CSF expression in the setting of hyperoxic stress

Abstract: Pulmonary expression of granulocyte/macrophage colony-stimulating factor (GM-CSF) is critically important for normal functional maturation of alveolar macrophages. We found previously that lung GM-CSF is dramatically suppressed in mice exposed to hyperoxia. Alveolar epithelial cells (AEC) are a major source of GM-CSF in the peripheral lung, and in vivo hyperoxia resulted in greatly reduced expression of GM-CSF protein by AEC ex vivo. We now explore the mechanisms responsible for this effect, using primary cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
28
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 36 publications
4
28
1
Order By: Relevance
“…Similarly, in primary AEC GM-CSF expression is greatly reduced during oxidative stress. Our recent studies have shown that this decreased expression is due to accelerated turnover of GM-CSF mRNA (9). In the present study we have provided new information concerning the mechanisms by which expression is suppressed in response to oxidative stress.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Similarly, in primary AEC GM-CSF expression is greatly reduced during oxidative stress. Our recent studies have shown that this decreased expression is due to accelerated turnover of GM-CSF mRNA (9). In the present study we have provided new information concerning the mechanisms by which expression is suppressed in response to oxidative stress.…”
Section: Discussionmentioning
confidence: 50%
“…Regulation of AEC GM-CSF mRNA Turnover-Mechanistic studies have indicated that an increase in mRNA turnover is a key step in the suppression of GM-CSF expression during oxidative stress (9). We have found that that addition of recombinant GM-CSF protein during hyperoxia reversed this suppression ( Fig.…”
Section: Regulation Of Aec Gm-csf Expression-mentioning
confidence: 73%
See 2 more Smart Citations
“…We and others have previously demonstrated that AECs are a substantial source of GM-CSF in the inflamed distal lung (39,40), and GM-CSF was shown to be induced in a TLR-dependent way in alveolar epithelium following bacterial challenge in vitro (41). Nonetheless, leukocytes of lymphoid and myeloid lineages, especially resident macrophages, were also found to be sources of GM-CSF in inflamed tissues (42).…”
Section: Discussionmentioning
confidence: 88%